KOMUNIKASI DALAM PROGRAM TALK SHOW DI TELEVISI : Kajian Perbandingan Komunikasi Talk Show Dan Komunikasi Langsung - Jamaluddin Nasution (Balai Bahasa Sumatera Utara, 2019)
The objectives of the study are to find out the types, the difference, and the reasons of conversational maxims occurring in the talk show. This research was conducted by qualitative content analysis method. The data were three topics of Mata Najwa namely politics, law, and education with different guests culture; Javanese, Makassar, Bataknese, and Chinese. The findings showed that all kinds of conversational maxims, i.e. quality, quantity, manner, and relevance, occurred in all topics and guests. Conversational maxims occurring in topic of politics is dominantly violated maxim of relevance, in topic of law is dominantly obeyed maxim of relevance, in topic of education is dominantly violated maxim quantity. Conversational maxims occurring with the Javanese guests is dominantly violated maxim of relevance, with the Makassar, Bataknese, and Chinese guests are all dominantly violated maxim of quantity. There are no relationship between culture and language tradition of the guests and their conversational maxims because the guests of Makassar, Bataknese, and Chinese have the same violation of maxim of quantity and all different guests have the same abstain obedience of maxim of manner. Factors affecting conversational maxims found are (1) The language attitude of the guests as participants in answering, (2) tendency to hide something or not to reveal truly, (3) making a joke or humorous answer, (4) using the metaphorical words in comparing or using language features, and (5) the issues of the topic itself.